Multi Tafsir Dan Celah Hukum Konsep Kedewasaan Dalam Undang-undang Nomor 1 Tahun 1974 Tentang Perkawinan - Rayno Dwi Adityo (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2015)
Inside the national law that the person can obtain a legal rights, given when someone could and capable in law. One of the aspect is maturity (meerdejarig) and maturation (minderjarig). About maturity and maturation has be regulated in Undang- undang No. I Tahun 1974 Tentang Perkawinan. Someone with maturity will determine rights and they liability can implemented according to the law. Allowing Hum both aspect will have broad impact in the proceedings of law. The reality, limitation of maturity age wich are contained on regulation found a diverse indicators a person to be an adult. In tact if pcrecivable things contextually, then we can comprehend someone age restrictions staten of maturity as necessary, example if somenone want to married by the permission of parents at age of twenty one years, on the relations of married dispensation at age nineteen years old of male and sixteen years old for female and in the border parent responsibility to children that was called adult is at age of eighteen years old. That was have disparity legal opinion in its interpretation. Some legal scholar have an difference opinion about limit of age inside the rule of marriage is not obvious and intersect. Therefore need to reviewed for uniformity so can dosing a fissure of law which may used to negative necessity of consequences law cavity and avoiding the impacts in the citizens.